Review on agronomic investigations on cardamom and cardamom-based cropping systems in Karnataka: Agronomic investigations on cardamom based cropping systems - Korikanthimath, V S; Krishnamurthy, K S (Journal of Spices and Aromatic Crops, 2022)
Small cardamom (Elettaria cardamomum Maton), an eco-friendly high value spice and foreign exchange earner, is a native of Western Ghats of South India. India enjoyed near monopoly in its production till the seventies, but with the emergence of Guatemala as the main competitor, it has been relegated to second position both in production and export. The low production of cardamom up to eighties was due to lack of sound location specific agronomic package of recommendations. Hence, after a detailed survey of entire small cardamom growing areas in India and interaction with cardamom growers and other stake holders, a comprehensive location specific research programme was finalised and carried out for over 25 years. As a consequence of detailed agronomic investigations on cardamom and cardamom-based cropping systems, various agro techniques such as selection of elite lines of cardamom, rapid clonal multiplication technique, nursery techniques, systems and season of planting, irrigation, shade and weed management, apiculture, harvest and post harvest techniques, multistoried cropping system involving cardamom, coffee, arecanut, coconut etc. evolved. These high production technologies were effectively transferred to the cardamom growers based on local specificity which resulted in higher yields (average of 750 kg dry capsules ha-1 and a potential yield of 1945 kg dry capsules in demonstrations in farmers fields in Kodagu, Karnataka) from an initial benchmark average yield of 120-140 kg dry capsules ha-1.